Guava Leaf Extract Exhibits Antimicrobial Activity in Extensively Drug-Resistant (XDR) Acinetobacter baumannii - Daniela Gutierrez-Montiel; Alma L. Guerrero-Barrera; Flor Y. Ramírez-Castillo; Fabiola Galindo-Guerrero; Ingrid G. Ornelas-García; Norma A. Chávez-Vela; Matheus de O. Costa; Francisco J. Avelar-Gonzalez; Adriana C. Moreno-Flores; Erick Vazquez-Pedroza; José M. Arreola-Guerra; Mario González-Gámez (Molecules)
Currently, a global health crisis is being caused by microbial resistance, in which Acinetobacter baumannii plays a crucial role, being considered the highest-priority microorganism by the World Health Organization (WHO) for discovering new antibiotics. As a result, phytochemicals have emerged as a potential alternative to combat resistant strains, since they can exert antimicrobial activity through various mechanisms and, at the same time, represent a more natural and safe option. This study analyzes the antimicrobial effects of guava leaf extract in ten clinical isolates of extensively drug-resistant (XDR) A. baumannii, using the agar diffusion technique and the microdilution method to determine the minimum inhibitory concentrations (MICs). Additionally, possible improvements in antimicrobial activity after the purification of polyphenolic compounds and potential synergy with the antibiotic gentamicin are examined in this research. Moreover, the effect of the plant extract in cell line A549 derived from lung tissue was also evaluated. The extract exhibited antimicrobial activity against all the strains studied, and the purification of polyphenols along with the combination with gentamicin improved the extract activity. The presence of the plant extract induced morphological changes in the lung cells after 24 h of exposure. Therefore, Psidium guajava L. leaf extract is a potential antimicrobial agent.